Slovene as a foreign language - Stritar Kučuk, Mojca (Slovenski jezik, 2009)
A learner corpus is an electornic collection of texts produced by non-native speakers learning a certain language. The article presents the pilot Slovene learner corpus PiKUST. Its design has faced two major challenges: the development of a reasonable set of criteria for collection and selection of learner material, and the development of an error annotation scheme. The error taxonomy and tagging procedure are described and, finally, the aplication of corpus results to teaching material is demonstrated.\
Keywords: Corpus linguistics; korpusi; korpusno jezikoslovje; Slovene; slovenščina; slovenščina kot drugi ali tuji jezik